Pendidikan Islam dalam Peningkakan Kualitas Sumber Daya Manusia Indonesia - Dodi Irawan; Nyimas Yunierti Prihatin; Rika Hasmayanti Agustina (PAI RAFAH, 2025)
This study explores the role of Islamic education strategies in enhancing the quality of human resources in the modern era. Humans are regarded as unique beings endowed with the potential to develop holistically spiritually, intellectually, and physically. Islamic education addresses this through two interconnected strategic models: macro and micro strategies. The macro strategy involves systemic efforts, including three core components: (1) the ultimate goal of Islamic education, which is to form pious individuals and a righteous society; (2) the foundational principles that guide the development of a curriculum rooted in Islamic values; and (3) policy priorities such as ensuring equal access to education for all children, diversifying educational pathways, reviewing and improving educational materials and methods, reinforcing religious education, strengthening educational administration and planning, and fostering regional and international cooperation among Islamic nations. The micro strategy, on the other hand, centers on tazkiyah al-nafs (purification of the soul), which aims to nurture personal discipline and moral character. This process cultivates inner balance by aligning the soul, mind, and body, ultimately fostering ethical awareness, resilience, and self-regulation.Together, these strategies form a holistic framework that equips individuals not only with knowledge and technical skills but also with strong moral and spiritual foundations. In the face of modern challenges—ranging from ethical dilemmas to rapid technological changes—Islamic education offers an integrative approach to developing high-quality human resources who are intellectually competent, morally upright, and spiritually grounded.